2019
DOI: 10.2474/trol.14.179
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Sliding Surface Pressure Measurement of Piston Ring under Reciprocating Condition Using Thin-Film Sensor

Abstract: In the tribology of mechanical elements using lubricating oil, verification of the dynamic surface pressure distribution during sliding operation is necessary in order to elucidate the sliding condition. The same also applies to the piston rings which are the sliding part of compression reciprocating device. Although some verification case in static condition or limited sliding area has been studied, there are many unknown aspects in this field. The thin-film sensor, since it has small influence on the shape o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Experimental studies [15][16][17][18] have shown the importance of measuring the friction force of pneumatic and hydraulic actuators, taking into account physical factors such as speed, pressure and other tribological factors. The authors [19] used a thin-film pressure sensor applied to the sliding surface of the piston ring to measure the instantaneous pressure distribution during the sliding of the piston ring on the cylinder liner. The paper [20] presents the importance of proper lubrication conditions with plastic grease and the properties of the seal material for wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies [15][16][17][18] have shown the importance of measuring the friction force of pneumatic and hydraulic actuators, taking into account physical factors such as speed, pressure and other tribological factors. The authors [19] used a thin-film pressure sensor applied to the sliding surface of the piston ring to measure the instantaneous pressure distribution during the sliding of the piston ring on the cylinder liner. The paper [20] presents the importance of proper lubrication conditions with plastic grease and the properties of the seal material for wear resistance.…”
Section: Introductionmentioning
confidence: 99%